The Strategy of Interfaith Education Figures in Managing Religious Tolerance in Banuroja Village, Gorontalo - Manahung, Muh. Ramoen; Solong, Najamuddin Petta; Datunsolang, Rinaldi; Hasiru, Roy; Tilome, Apris A. (Interdisciplinary Social Studies, 2022)
Background: Interfaith education figures inevitably have significant role in managing religious tolerance because education is carried out both in and outside schools. Interfaith figures in society not only actualize and internalize religious values but also implement strategies for balancing the potential of nature so that the humanity of religious communities is maintained. Aim: This paper is the result of research examining interfaith education figures’ strategies in managing tolerance in Banuroja Village, Randangan District, Pohuwato Regency. Method: The researchers applied qualitative approach with phenomenological design. The data collection techniques of this research were observation, interview, documentation, and Focus Group Discussion. Research data was tested by thorough observation and triangulation, both source and method triangulation. Findings: The results of this research indicate three strategies of interfaith education figures in managing tolerance in Banuroja Village, Pohuwato Regency, they are: first, the assimilation strategy, carrying out a blend of cultures or assimilation of life, for example when maintaining security at the neighborhood-watch post (poskamling) by wearing traditional uniforms. Second, the mutual need strategy is embedding a culture of interethnic and religious mutual cooperation as the basic foundation for cultural resilience and the creation of distributive justice. Third, the educative communication strategy is the involvement of educators regardless of their religion in various activities and educative communication. In a pluralist and heterogeneous society like Banuroja, interfaith education figures who are full of knowledge and educational methods have a very strategic, urgent, and beneficial position for the community at large.